Serum Phosphate and Microvascular Function in a Population-Based Cohort - Ginsberg, Charles (Clin J Am Soc Nephrol, 2019)
BACKGROUND AND OBJECTIVES: Higher serum phosphate is associated with cardiovascular events and all-cause mortality. Explanations of this association have focused on large vessel calcification and stiffness. Studies suggest that a higher serum phosphate induces microvascular dysfunction, but relationships in humans with direct measures of microvascular function are lacking. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We performed a cross-sectional analysis of 3189 community-living participants that underwent skin capillaroscopy, laser-Doppler flowmetry, and flicker light–induced retinal vessel responses. We used linear regression to assess the association between serum phosphate and each microvascular outcome. The primary outcome was skin capillary recruitment during postocclusive peak reactive hyperemia by capillaroscopy. Secondary outcomes included capillary recruitment during venous congestion, heat-induced skin hyperemic response, flicker light–induced retinal arteriolar, and venular dilation. RESULTS: The mean age of the cohort was 59±8 years, 48% were women, 7% had an eGFR <60 ml/min per 1.73 m(2), and the mean serum phosphate concentration was 3.2±0.5 mg/dl. A 1 mg/dl higher serum phosphate was independently associated with a 5.0% lower postocclusive capillary recruitment (95% CI, −10.0% to −0.1%). Results were similar for capillary recruitment with venous congestion (−4.5%; 95% CI, −9.8% to 0.7%). A 1 mg/dl higher serum phosphate was also independently associated with a 0.23% lower retinal venular dilation in response to flicker light (95% CI, −0.44% to −0.02%). A higher serum phosphate was not associated with change in flicker light–induced retinal arteriolar dilation or heat-induced skin hyperemic response, however a higher serum phosphate was associated with a lower heat-induced skin hyperemic response among men (−149% [95% CI, −260 to −38] per 1 mg/dl higher serum phosphate) but not women (P interaction, 0.01). CONCLUSIONS: Higher serum phosphate concentrations, even within the normal range, are associated with microvascular dysfunction in community-living individuals. PODCAST: This article contains a podcast at https://www.asn-online.org/media/podcast/CJASN/2019_09_20_CJN02610319.mp3